Evolution of an adenine-copper cluster to a highly porous cuboidal framework: solution-phase ripening and gas-adsorption properties - Venkatesh, V.; Pachfule, Pradip; Banerjee, Rahul; Verma, Sandeep (Chemistry-A European Journal, 2014)
The synthesis and directed evolution of a tetranu-clear copper cluster, supported by 8-mercapto-N9-propyladenine ligand, to a highly porous three-dimensional cubic framework in the solid state is reported. The structure of this porous framework was unambiguously characterized by Xray crystallography. The framework contains about 62% solvent-accessible void; the presence of a free exocyclic amino group in the porous framework facilitates reversible adsorption of gas and solvent molecules. Oriented growth of framework in solution was also tracked by force and scanning electron microscopy studies, leading to identification of an intriguing ripening process, over a period of 30 days, which also revealed formation of cuboidal aggregates in solution. The elemental composition of these cuboidal aggregates was ascertained by EDAX analysis.
Keywords: cuboidal frameworks; gas adsorption; metal-organic frameworks; Ostwald ripening; solution-phase ripening